The impact of consignment-based marketing through middlemen on the economic sustainability of farmers in Pawenang Village, Nagrak Subdistrict, Sukabumi Regency - Tri Sanatha Wahyu Akbar; Riani Winarni; Galih Raspati; Mulfi Sandi Yuda; Bayu Prastiyo Nurdiana (Priviet Social Sciences Journal, 2025)
The consignment-based marketing system through middlemen (known locally as tengkulak) has long been practiced by farmers in Nagrak District, particularly in Pawenang Village. This system offers certain advantages, such as lower costs, operational simplicity, no need for technological skills, and delegation of distribution responsibilities to middlemen. However, the dominance of middlemen in the agricultural marketing chain leads to a high level of farmer dependency. Middlemen control nearly the entire market, leaving farmers with little to no bargaining power when they sell the middlemen take 10% of the final selling price. Limited market access also prevents farmers from tracking price fluctuations, thus making them vulnerable to price manipulation. Moreover, farmers are charged with the distribution costs. This situation negatively affects farmers’ welfare, with most living under economic hardship, even though agriculture is their primary source of income. This study aims to analyze the impact of the consignment marketing system through middlemen on the economic sustainability of farmers in Pawenang Village. The findings are expected to provide insights into how this system affects farmer independence and offer alternative marketing solutions to reduce dependence on middlemen, thereby improving the competitiveness and sustainability of agricultural enterprises.